Growth, Productivity, and the Rate of Returnon Capital - Chadha, Bankim (IMF Working Papers; Working Paper ;, 1992)
This paper examines the ability of alternative classes of growth models to explain the historical experience of the U.S. economy. The potential returns to the U.S. from raising its investment rate in terms of both the level and growth rate of future output are then quantified. The long-run growth performance of the U.S. economy is found to be broadly consistent with the predictions of the neoclassical growth model. Endogenous growth models, which suggest a larger contribution of capital to growth and long-run effects of investment on the growth rate, do not seem to be supported by the data.